Examination of cross contamination risks between hospitals by external medical staff via cross-sectional intercept survey of hand hygiene - Schiffers, Hank; Zaatreh, Sarah; Mittelmeier, Wolfram; Bader, Rainer (German Medical Science GMS Publishing House, 2014)
[english] Introduction: Work in hospitals is supported by contributions of life sciences industry representatives (IR) in various ways of fields. Close contact between them, caretakers and patients is unavoidable, even in situations where hygiene is critical.The present study investigates whether IR display comparable levels of and methicillin-resistant (MRSA) contamination after being exposed to a shared environment for a minimum of 4 hours.Material and methods: An anonymous survey to sample a group of healthcare professionals for traces of fingertip contamination was performed. We used dip slides ( and MRSA) to evaluate professionals at the medical exhibition MEDICA. After applying exclusion criteria 298 participants remained valid, they consisted of 208 industry representatives, 49 nurses and 41 physicians.Results: IR where engaged in hospitals, operating rooms and outpatient clinics (82%, 41.8%, 51.9% respectively). 65.9% of IR (vs. 48.8% physicians and 40.8% nurses) carried a microbiological burden ≥10 CFU (colony forming units). Neither (≥10 CFU) in IR (40.9%) did show statistical differences in contamination patterns in comparison to physicians (43.9%, p=0.346) and nurses (36.7%, p=0.878) nor did MRSA (physicians p=0.579, nurses p=0.908). We were unable to differentiate transient from pre-existing permanent colonization.Conclusion: Exposure to the same environment may result in similar hand contamination patterns of IR when compared caregivers. This supports the concern that industry representatives can cause cross infection between hospitals and hygiene sensitive areas like operation room, intensive care unit and central sterilization units particularly. Further study is required to clarify whether pre-existing bacterial colonization is an influencing factor and how industry is taking care of this to create a safe working environment for their employees, the customers and ultimately the patients.